REACTIVE BLOOD DONOR NOTIFICATION; THEIR RESPONSES AND PERCEPTIONS: EXPERIENCE FROM SOUTHERN PAKISTAN - Raza, Naila; Qureshi, Hina; Qureshi, Ambrina (Journal of Ayub Medical College Abbottabad, 2018)
Background: Donor notification of reactive status is important to prevent the spread of disease. Response of reactive donors to seek confirmation and treatment is a direct reflection of their knowledge and attitudes towards transfusion transmittable infections. Method: A cross sectional observational study was conducted from August 2014 to July 2015 at the blood bank of a tertiary care hospital, Karachi, Pakistan. Reactive donors’ notification and responses were noted with reasons of failure. A cross-sectional analytical survey with non-probability purposive sampling was done on 350 potential consenting blood donors using a pre-tested questionnaire to assess their knowledge and attitude about disease awareness, transmission routes, financial implications and disease sensitization. Result: Out of 16660 donations, 5.57% were rejected on positive screening tests. Repeat donors (69.5%) with primary to secondary qualifications constituted the bulk of reactive donors. Donor notification rate were 54.25% whereas 28.68% donors responded to blood bank in person. The survey showed limited awareness about transfusion transmitted infections. Respondents who were ignorant of disease spread through blood transfusion comprised of 48%. 96.6% donors did not know the financial impact of treatment and 69.7% were unable to afford it. Moreover, 94.9% donors were not protected against hepatitis B. Participants with secondary education had significantly less odds of being adequately knowledgeable (OR=0.372, 95% CI: 0.203-0.681, p value <0.01) but more likely to have a positive attitude. Conclusion: There is need for structured pre-donation counselling to sensitize donors about transfusion related diseases in resource limited countries where treatment costs are high and out of reach for most donors. Keywords: Blood donors; Donor notification; Transfusion transmittable diseases